Cardio Renal Syndrome (SCR) - Flores-Esteves, Luis (2019)
The present clinical research work related to Cardio Renal Syndrome (SCR) has been carried out in theNephrology Service and the Intensive Care Unit of the Father Luis Tezza Clinic, during the period from 2013 to 2019. The present research is the clinical experience in the management of the diagnostic and therapeutic protocols implemented, and the results obtained, in 15 patients grouped in three for each of the five groups according to the current concepts of the last decade, in the international context. The epidemiological aspect, the pathogenesis is described in its reciprocal interaction either acute or chronic between cardiac, renal failures and systemic processes that also affect both organs in this syndrome. An exhaustive review of the pathophysiology is made in its hemodynamic aspects, alterations in the pathophysiology is made in its hemodynamic aspects, alterations in the markers or hepato renal syndrome, cancer, renal transplantation, among others. The results and conclusions obtained are communicated and the urgent need to form anintegrated cardiorenal committee is recommended, which strengthens future cardiorenal trials, integrates clinical needs and encourages future research in this important field.